UK government and politics - MacNaughton, Neil; Cooper, Toby (Hodder Education, 2021)
This fully updated Textbook for Pearson Edexcel A-level Politics will help your students develop a critical understanding of the latest developments in UK Government and Politics. This trusted textbook by Neil McNaughton, revised by Toby Cooper, is specially designed to reflect the Edexcel specification and help your students approach complex topics with confidence. This Student Textbook: - Comprehensively covers Government of the UK and Politics of the UK, including the 2019 General Election and the Brexit process - Places recent developments in a historical context throughout to show the influence of political history on current events - Builds your confidence by highlighting key terms and explaining synoptic links between different topics in the specification - Develops your analysis and evaluation skills through debates and practice questions - Provides answer guidance for practice questions online at www.hoddereducation.co.uk Hodder Education textbooks covering the Core and Non-Core Political Ideas are available to complete your students' studies for Components 1 and 2 of the Pearson Edexcel specification. Core and Non-Core Political Ideas are compulsory elements of Components 1 and 2.